METHODOLOGY OF IMPROVING COMMUNICATIVE COMPETENCE STUDENTS’ OF THE MEDICAL UNIVERSITY (BASED ON THE TOPIC ‘STENOCARDIA’) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-4-173-184The most effective principles of the organization and intensification of the educational process on the subject of "Scientific style of speech" (Russian as a foreign language) are described. The development of a set of exercises of pre-text, pre-text and post-text exercises aimed at systematization and consolidation of knowledge, as well as the development of communication skills in a foreign language of future doctors (foreign medical students of the Faculty of Medicine 2-3 courses, topic "Angina pectoris", section "Patient Survey") is presented. Keywords: medical record, patient survey, role-playing game, communication, teaching method, methodology, specialty language, Russian as a foreign language.Key words: medical record, patient survey, role-playing game, communication, teaching method, methodology, specialty language, Russian as a foreign language